Pengaruh Literasi Keuangan Dan Financial Technology Terhadap Keputusan Berinvestasi Melalui Minat Investasi Sebagai Variabel Mediasi - Huda, Miftahul; Susanti, Susanti (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
The development of technology in Indonesia is now increasingly rapid, technology has become a positive and negative value for business people and others. Based on the data received, the dominant technology in Indonesia has increased. So this research aims to analyze the influence of financial literacy and financial technology on investment decisions through investment interest as a mediating variable. This research method uses quantitative with a sample size of 116 respondents who are the millennial generation in Malang Regency with data collection techniques in the form of questionnaires which are distributed offline and then tested instruments in the form of validity and reliability tests with data analysis techniques using path analysis. The results obtained are Financial literacy and financial technology influence investment decisions through investment interest as a mediating variable. This shows that both have a positive impact on investment interest, which plays a significant role as a mediator in investment decisions